Diagnostic study for Toxoplasmosis by Serological test and PCR technique in Kirkuk province - Fatin M. Nawwab Al-Deen; Mohammed A. Kadir; Rafae Z .Mukhlif Al-Sugmiany (Tikrit Journal of Pure Science)
Background: Severe Toxoplasma gondii infection in early pregnancy brings the risk of transferring the infection to the unborn baby with serious abnormality. The aim of identifying toxoplasmosis in early stage is to recognize mother-to-infant transmission for early cure to avoid undesirable complication. Using serological test to determine anti-Toxoplasma specific IgG and IgM antibodies possibly may not identify new or even previous infection. However, many molecular techniques are now being extensively used through the world among these methods polymerase chain reaction PCR technique emerged as the most widely accepted method for directly detection infectious agents. Thus, the goal in this study is to compare immunoassay by indirect (IgM and IgG) detection diagnostic technique and conventional PCR as molecular assay in diagnosis of T. gondii in whole blood of aborted females in Kirkuk province-Iraq.